Hybrid LTE-Vanets Based Optimal Radio Access Selection - Harum, Norharyati; Abu, Nor Azman; Ali, Mohanad Faeq (Asian Research Publishing Network (ARPN), 2018)
The access technology selection,that a user can associate with any radio access technology (RAT) with the availability of multiple RATs available,has been intensively investigated by vehicular Ad hoc Network (VANET).In particular it carries and distributes information,inter-communicates and is capable of communicating with other stationary units deployed along roadways.The current study proposed hybrid optimal radio access selection algorithm (ORAS) for LTE/VANETs network. The periodically broadcasted network information supports mobile users to make their selection decisions;mobiles consider their own individual preferences,cost and partial QoS information signaled by the network while making their decision.The switches algorithm between VANET and LTE based on the load value of network and quality of service requirements were proposed.The simulation results have shown that the proposed algorithm has better performance compared with LTE and VANETs separately in terms of packet delivery ratio,latency and application-level throughput.